2021
DOI: 10.1002/jcsm.12818
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and long‐term outcomes after incident stroke: a prospective population‐based cohort study

Abstract: Background The association between obesity, major adverse cardiovascular events (MACE), and mortality in patients with incident stroke is not well established. We assessed the relationship between body mass index (BMI) and MACE in patients with incident stroke. Methods The population‐based cohort study identified 30 702 individuals from the Clinical Practice Research Datalink (CPRD GOLD) and Hospital Episode Statistics (HES) databases from the United Kingdom. Individuals were aged ≥18 years with incident strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
3
12
0
1
Order By: Relevance
“…This analysis confirms several previous reports which showed that increasing BMI was associated with better outcomes in patients with existing cardiovascular disease 4 . The study extends current knowledge by showing that in patients with cardiovascular disease, this association of body weight and outcome is not influenced by the level of metabolic health, that is, the presence of classical metabolic risk factors including dyslipidaemia, diabetes mellitus or arterial hypertension 14–16 . Indeed, similar findings were reported in patients with diabetes mellitus 17 or pre‐diabetes 18 …”
Section: Discussionsupporting
confidence: 90%
“…This analysis confirms several previous reports which showed that increasing BMI was associated with better outcomes in patients with existing cardiovascular disease 4 . The study extends current knowledge by showing that in patients with cardiovascular disease, this association of body weight and outcome is not influenced by the level of metabolic health, that is, the presence of classical metabolic risk factors including dyslipidaemia, diabetes mellitus or arterial hypertension 14–16 . Indeed, similar findings were reported in patients with diabetes mellitus 17 or pre‐diabetes 18 …”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, there is a paradox in incident stroke patients associated with obesity or overweight. In these patients, the prognosis is more favorable for major adverse cardiovascular events, such as coronary heart disease, recurrent stroke, peripheral vascular disease, heart failure, and cardiovascular-related mortality [ 97 ]. In the treatment of these patients with obesity and CVDs, semaglutide has been evaluated by the Semaglutide Effects on Cardiovascular Outcomes in People with Overweight or Obesity (SELECT) study [ 98 ].…”
Section: Dynapenic and Sarcopenic Obesity And Their Association With ...mentioning
confidence: 99%
“…Currently, the association between obesity, metabolic dysfunction, neuroinflammation, and mortality in stroke patients is not well-established; however, some cohort studies have shown a correlation between body mass index and abdominal obesity with ischemic and hemorrhagic stroke (Shiozawa et al 2021 ; Akyea et al 2021 ; Jaakonmäki et al 2022 ). For all these reasons, this review aims to analyze how obesity-related systemic inflammation can affect microglial response in the CNS, prime them, leading to increased stroke-associated neuronal damage secondary to obesity and chronic neuroinflammation, linking them as risk factors that decrease survival and worsening patient’s prognosis as correlated in epidemiological studies (Shiozawa et al 2021 ; Akyea et al 2021 ; Jaakonmäki et al 2022 ). Herein, we review the roles of microglia and their functional interactions and regulatory mechanisms in obesity and stroke, and how obesity-primed microglia could enhance stroke-associated damage.…”
Section: Introductionmentioning
confidence: 99%